A Fully Automatic Novel Method to Determine QT Interval Based on Continuous Wavelet Transform - Yilmaz, Cuneyt; Iscan, Mehmet; Yilmaz, Abdurrahman (ISTANBUL UNIV, FAC ENGINEERING, 2017)
Nowadays, automatic recognition algorithm is being frequently utilized to extract the information concerning cardiac abnormalities. In this study, a fully automatic novel method based on the continuous wavelet transform (CWT) was developed for QT intervals in various ECG signals. Especially, the determination of T-wave end is the paramount problem to be solved. The developed method was performed to find the beginning of QRS complexes and the end of T-wave. The proposed algorithm was tested on MIT-BIH-NSR database given by QT database, then, it yielded the scores 15.17 milliseconds and root-mean-square error of 17.19 milliseconds at silver standard, 19.22 milliseconds and 20.22 milliseconds at gold standard, respectively. In conclusion, the proposed algorithm is a fully automatic method to attain a high performance in the calculation of QT intervals at various ECG signals.
Keywords: ECG Signal; QT interval; ECG signal classification; Pan-Tompkins Algorithm; Continuous Wavelet Transform; ELECTROCARDIOGRAMS; ALGORITHM; LOCATION; Engineering